Ecological knowledge and awareness of parents and their children in primary schools’ third classes - Parlak, Mirosława (Studia Ecologiae et Bioethicae, 2016)
Nowadays the implementation of the ecological education content is particularly significant. It is important to shape a child’s environmental awareness, sense of responsibility, respect and a willingness to work for nearest environmental profit. Teacher’s and parent’s duty is to stimulate a sensitivity and emotional attitude to nature and to introduce child to a world of values. Particularly important are the attitudes of parents towards nature protection, because they have a direct impact on the attitudes of their children. The research compared the ecological awareness and the extent of that awareness among children in third classes in primary schools and their parents. The results in both groups prove that youngsters are more aware, and the older generation’s knowledge and awareness is still not satisfying. Therefore, it can be assumed that what the children have learned is the effect of their teachers and school efforts.